2022
DOI: 10.3389/fped.2022.999274
|View full text |Cite
|
Sign up to set email alerts
|

Natural history and neurodevelopmental outcomes in perinatal stress induced hyperinsulinism

Abstract: ObjectiveTo describe perinatal stress induced hyperinsulinism (PSIHI), determine the prevalence of neurodevelopmental differences, and identify risk factors for poor developmental prognosis.MethodsSubjects with a history of hyperinsulinism (HI) and perinatal stress and in whom resolution of the HI was demonstrated were included. Medical record review, caregiver interview, and three validated developmental assessments were completed.ResultsOf the 107 subjects (75% male), 36% were born between 32 and 37 weeks. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Unauthorized distribution is strictly prohibited. maximum GIR reported were 11.7 and 10.0 mg • kg -1 • min -1 , respectively, in a recent study [13].…”
Section: Accepted Manuscriptmentioning
confidence: 81%
See 2 more Smart Citations
“…Unauthorized distribution is strictly prohibited. maximum GIR reported were 11.7 and 10.0 mg • kg -1 • min -1 , respectively, in a recent study [13].…”
Section: Accepted Manuscriptmentioning
confidence: 81%
“…Neonatal hypoglycemia may have long-term consequences that may not be detected until school age [25][26][27][28]. Higher target levels of glucose concentration are currently used for patients with hyperinsulinemia because of lack of alternative fuels [12,13]. There is considerable heterogeneity across studies about which level of hypoglycemia is associated with longterm consequences; controversy may not be resolved until school age outcomes are available for the randomized trial by van Kempen et al [29].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of concentrated dextrose, continuously via gastric tube in infants with hyperinsulinism who are not responsive to medication or pancreatectomy 22 or newborns diagnosed with perinatal stress-induced hyperinulinism 23 has been reported and almost one-fifth of respondents reported use of enteral dextrose, not gel, as treatment. While there are no data on the efficacy and safety of enteral dextrose use in transient hypoglycemia, especially in premature newborns, we speculate this finding might be due to an attempt to avoid the use of intravenous dextrose.…”
Section: Discussionmentioning
confidence: 99%
“…The reported prevalence of neurodevelopmental differences in children with HI ranges 26–48% in different cohorts from around the world [38]. Sigal et al showed that children with perinatal stress-induced HI (in whom hypoglycemia exposure is limited to the first months of life) experience similar rates of adverse neurodevelopment [39 ▪ ]. Rapid advances in the monitoring and therapeutic landscape for HI holds promise to improve these outcomes, and new approaches to assess long-term impact have emerged.…”
Section: Discussionmentioning
confidence: 99%